The role of the gastrointestinal tract in toxigenic Clostridium tetani infection: a case-control study - Van Hao, N; Huyen, NNM; Ny, NTH; Trang, VTN; Hoang, NVM; Thuy, DB; Nguyen, NT; Lieu, PT; Duong, HTH; Thuy, TTD; Nhat, PTH; Tam, DTH; et al. (American Society of Tropical Medicine and Hygiene, 2021)
Tetanus arises from wound contamination with Clostridium tetani, but approximately one fifth of patients have no discernable entry wound. Clostridium tetani is culturable from animal feces, suggesting the gastrointestinal tract could be an endogenous reservoir or direct-entry portal, but human data are lacking. In this study of 101 Vietnamese adults with tetanus and 29 hospitalized control subjects, admission stool samples were cultured for C. tetani. Anti-tetanus toxin antibodies were measured by ELISA. Clostridium tetani toxigenicity was evaluated using polymerase chain reaction and sequencing. Toxigenic C. tetani was cultured from stool samples in 50 of 100 (50%) tetanus cases and 12 of 28 (42.9%) control subjects (P = 0.50), and stool samples of 44 of 85 (52.4%) tetanus cases with clinically identified wounds compared with 6 of 15 (47.6%) patients without clinically identified wounds (P = 0.28). Nine of 12 (75%) control subjects with toxigenic C. tetani in their stool samples lacked protective antibody concentrations. These findings fail to show evidence of an association between gastrointestinal C. tetani and tetanus infection, but emphasize the importance of increasing vaccination coverage.